Plan de comunicación de gestión en crisis para Petrotech Group - Pérez Miño, Sofía Cristina (2013)
The present study on the company PETROTECH GROUP analyzes the significance and impact of crises on business performance. For this the communication, reputational and strategic management components will be studied, as well as their roles in critical situations. The importance of determining the types and phases of crises are evident when planning scenarios and prevention activities. The significance of the Committee of crisis and particularly the performance of Speaker in the relationship with the media and other stakeholders will be detailed. Through an exploratory – descriptive study of the company, parameters and the scope of the investigation were determined. By verifying the population universe and selecting a sample, the variables and research tools were obtained to help identify the types of crises that could affect the organization and to propose a crisis management plan for each. This plan aims to design the actions and strategies to be implemented at critical moments. With the identification of 11 types of potential crises, classified into three groups, crisis management practices will be identified to anticipate and resolve situations that affect the development of the company. By promoting polices of crisis, the plan intends to engage staff, allocate resources, provide information to employees, maintain an open internal communication and plan for crisis management simulations. During a crisis, the Committee will be activated and it will focus on maintaining an image of trust among its stakeholders, being the official source of information, training its employees to face the situation and implementing a crisis management plan. To prevent and control a crisis, a prevention plan is presented, whose management includes two programs: one related to Public Relations and the other related to Communication and training. Additionally, a communication campaign is incorporated to support actions to prevent a possible crisis. This campaign includes the strengthening of the security training program, as well as PETROTECH GROUP's corporate identity. A section of activities, schedule and budget for both the campaign and the crisis management plan is allocated. Finally, a list of conclusions and recommendations as a contribution to this study is included.